2015
DOI: 10.29137/umagd.346107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nepheline Syenite Addition on Sanitaryware Body

Abstract: Abstr act The effect of the addition of Nepheline syenite on the sinter ing, and pr oper ties of a sanitar ywar e por celain body was studied. Two cer amic bodies wer e compar ed: a commer cial sanitar ywar e body and one, wher e 40% of the mass of Na feldspar was substituted nepheline syenite. The sinter ing was evaluated by the linear shr inkage, the water absor ption. Samples, the bending str ength. The addition of Nepheline syenite had a positive effect on the for mation of the liquid phase dur ing the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…They obtained semi‐vitreous bodies with flexural strength of 78 MPa and water absorption of 0.4% for optimally maturated specimens. Kunduraci et al investigated the effect of nepheline syenite addition by substituting Na‐feldspar on the sintering and technological properties of sanitaryware porcelain bodies. They showed that the addition of nepheline syenite reduced the sintering temperature from 1230°C to 1180°C.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained semi‐vitreous bodies with flexural strength of 78 MPa and water absorption of 0.4% for optimally maturated specimens. Kunduraci et al investigated the effect of nepheline syenite addition by substituting Na‐feldspar on the sintering and technological properties of sanitaryware porcelain bodies. They showed that the addition of nepheline syenite reduced the sintering temperature from 1230°C to 1180°C.…”
Section: Introductionmentioning
confidence: 99%
“…Needle-shaped mullite crystals (secondary mullite, Type 2) were observed in NS1 [13]. Mullite needles formed in areas containing fine clays, feldspars and quartz [14]. Feldspar particles, kaolinitic clay, or clay agglomeration formed elongated needle-shaped crystals known as secondary mullite [15].…”
Section: Sem Analysismentioning
confidence: 99%
“…Nefelin siyenitlerin cam ve seramik sanayinde ham madde olarak kullanımına yönelik pek çok çalışma yapılmıştır [5]- [12]. Bu çalışmalardan bir kısmı özellikle nefelin siyenit kayasının içerisindeki istenmeyen minerallerin (demir oksit mineralleri) kabul edilebilir limitlerde nasıl zenginleştirilmesi gerektiği ile ilgilidir [9], [2].…”
Section: Introductionunclassified
“…Konu ile ilgili diğer çalışmalar ise nefelin mineralinin pişirme sıcaklığını düşürmesi üzerine yapılmıştır [12]. Kunduracı ve Aydın [12]; Na-feldispat ve nefelin içeren iki farklı seramik hammadde karışımı kullanarak deneysel çalışmalar yapmışlar ve birinci karışımın 1220 °C diğerinin ise 1190 °C'de piştiğini göstermişlerdir.…”
Section: Introductionunclassified
See 1 more Smart Citation